Study of trace organic contaminants (TrOcs) on the medicinal leaves of Eugenia uniflora L. from urban and forest-preserved areas (Research, Society and Development, 2025)
The organic pollutants promote significant risks to both human health and environmental sustainability. These compounds have seen a dramatic increase in diversity and quantity, infiltrating bodies of water, marine environments, and living organisms. Some factors contribute to pollutant emissions, such as road traffic and industrial activities and it leads to a spatiotemporal variability. Between the organic pollutants, Trace Organic Contaminants (TrOCs), which comprise a diverse range of industrial chemicals, pharmaceutical residues, and pesticides, are also gaining attention for their toxic effects on aquatic organisms and plants. Thus, this investigation aimed to evaluate the occurrence of TrOCs deposited in Eugenia uniflora leaves from urban areas and preserved forests during the four seasons of the year. Experimental, laboratory research, of a quantitative nature, was carried out. The identification of emerging trace organic contaminants was analyzed by Gas Chromatography - Mass Spectrometry (GC-MS) and Gas chromatography - Flame Ionization Detector (GC-FID). This analysis allowed us to identify TrOCs and some of them related to endocrine disorders. These TrOCs differed depending on the region and season of the year in which the leaves were collected, and they were present even in plants cultivated in preserved forests.